Analysis of Capital Structure and CAPEX : It’s Effect on ROE of Mining Companies - Eldina Ayu Trisnawati; Wahyu Maulana (Coopetition : Jurnal Ilmiah Manajemen, 2022)
The mining sector has assets to support the company's operations in order to make a profit. This requires large capital so that accurate calculations are needed so as not to have an impact on financial performance. The purpose of this study is to examine the effect of capital structure on ROE which is a reflection of the company's financial performance. The research population is mining sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period by analyzing published financial reports. The sample used purposive sampling method in order to obtain data that matched the desired criteria. The results showed that partially, the DER variable had a negative effect on ROE while the DAR variable had a positive effect on ROE and the CAPEX variable had no effect on ROE. The results of the study simultaneously show that DAR, DER and CAPEX have a positive effect on ROE